(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2022)
The changing nature of security risks and threats has conditioned a redefinition of Israel’s security policy, and it has also imposed the adoption of new security approaches. Acknowledging this reality, Israel must adapt to the new circumstances in order to protect its national interests and to achieve an optimal level of security. The adaptation of the security system to the new security environment should be an expression and a result of the general comprehensive inclusion of all subjects in charge of achieving security. In finding an optimal model for achieving security, it is necessary to start by perceiving the position and efficiency of the security system, while accepting security sector reforms as an adopted concept that includes a broad platform for the implementation and concretization of the specific tasks for the improvement of the internal structure of Israel’s security system.